Evaluation of NSE Price Data Using Reliability of Series Structure Model - Razak K, Abdul; K, Rajakumar (International Journal of Engineering and Technology, 2018)
Fluffy set based techniques have been turned out to be successful in taking care of numerous kinds of vulnerabilities in Â various fields, including dependability building. In any modern system, the reliability and cost are considered to be the most important factor and the reliability of the system may be twisted as linear or nonlinear programming. This paper deals the fluffy nonlinear reliability optimization problem for series structure model. The objective of this paper is to quantify the most extreme unwavering quality subject to leat cost using triangular fluffy number. As an illustration, system of five components NSE price data is analyzedÂ Â